Thyroid hormone resistance syndrome caused by heterozygous A317T mutation in thyroid hormone receptor β gene: Report of one Chinese pedigree and review of the literature. Issue 33 (August 2016) - Guo, Qing-Hua; Wang, Bao-An; Wang, Chen-Zhi; Wang, Min; Lu, Ju-Ming; Lv, Zhao-Hui; Mu, Yi-Ming
Abstract: Background: Thyroid hormone resistance syndrome (THRS) is a rare disorder with increased concentrations of free thyroxine (FT4) and triiodothyronine (FT3), but normal or slightly increased thyroid-stimulating hormone (TSH). The mutations in the thyroid hormone receptor β (THRβ) gene are thought to be the main pathogenesis. Objectives: The aims of this study were to present 1 pedigree of Chinese THRS, summarize their clinical characteristics, and analyze the gene mutation. Methods: The clinical characteristics and thyroid function of the proband and his family members were collected. Gene mutations were analyzed by DNA sequencing. Results: The proband and his mother exhibited symptoms of hyperthyroidism, such as palpitations, heat intolerance, and perspiration. The mother also had atrial fibrillation. The rest of the kindred did not display clinical manifestations of hyper- or hypothyroidism. DNA sequencing revealed a heterozygous G>A missense mutation at position 949 in Exon 9 of THRβ both in the patient and his mother, which led to the transition from alanine to threonine at position 317 of THRβ protein (A317T), whereas the rest of the kindred did not share this mutation. The proband and his mother were diagnosed with pituitary resistance to thyroid hormone. Oral administration of methimazole was stopped and β-receptor blockers were administrated. Conclusions: We present 1 pedigree of THRS with heterozygous A317T mutation in THRβ gene in the proband and his mother, which is the first reported mutation in Chinese and provides a comprehensive review of available literature.